2016
DOI: 10.2460/ajvr.77.8.890
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of cysteine protease inhibitors on Trichomonas foetus–induced cytopathic changes in porcine intestinal epithelial cells

Abstract: OBJECTIVE To investigate the effects of specific cysteine protease (CP) inhibitors on cytopathic changes to porcine intestinal epithelial cells induced by Tritrichomonas foetus isolated from naturally infected cats. SAMPLE T foetus isolates from 4 naturally infected cats and nontransformed porcine intestinal epithelial cells. PROCEDURES T foetus isolates were treated with or without 0.1 to 1.0mM of the CP inhibitors antipain, cystatin, leupeptin, and chymostatin and the vinyl sulfone inhibitors WRR-483 and K11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Following such recognition, the parasite synthesizes cytotoxic molecules that assist in colonization of the epithelium. These molecules include neuraminidases 98,99 , enzymes with sialidase activity that cleave sialic acid from the vaginal epithelium, thus exposing α-D-Nacetylgalactosamine residues. Infection with T. foetus modifies the expression of glycoconjugates in the genital epithelium of infected females, both in cattle 100 and in a murine model 101,102 ; and recently we found that these changes may vary upon infection with different T. foetus isolates and with different degrees of pathogenicity 103 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following such recognition, the parasite synthesizes cytotoxic molecules that assist in colonization of the epithelium. These molecules include neuraminidases 98,99 , enzymes with sialidase activity that cleave sialic acid from the vaginal epithelium, thus exposing α-D-Nacetylgalactosamine residues. Infection with T. foetus modifies the expression of glycoconjugates in the genital epithelium of infected females, both in cattle 100 and in a murine model 101,102 ; and recently we found that these changes may vary upon infection with different T. foetus isolates and with different degrees of pathogenicity 103 .…”
Section: Discussionmentioning
confidence: 99%
“…foetus, the presence of sialic acid on the surface of host cells is essential for its recognition and subsequent adhesion 98,99 . Following such recognition, the parasite synthesizes cytotoxic molecules that assist in colonization of the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…25 Cysteine proteases appear to mediate both adhesion and cytotoxic effects on the intestinal epithelium, and are being explored as possible treatment targets to ameliorate the clinical signs of infection. 68,78,79 Large scale studies to define the transcriptome and proteome of Tritrichomonas species to identify virulence factors and to screen large libraries of drugs for effectiveness in killing Tritrichomonas species are actively ongoing by several teams of investigators. 68,80…”
Section: Pathogenesismentioning
confidence: 99%
“…25 Cysteine proteases appear to mediate both adhesion and cytotoxic effects on the intestinal epithelium, and are being explored as possible treatment targets to ameliorate the clinical signs of infection. 68,78,79…”
Section: Pathogenesismentioning
confidence: 99%